High Di-rhamnolipid Production Using Pseudomonas aeruginosa KT1115, Separation of Mono/Di-rhamnolipids, and Evaluation of Their Properties - Zhou, Jie; Xue, Rui; Liu, Shixun; Xu, Ning; Xin, Fengxue; Zhang, Wenming; Jiang, Min; Dong, Weiliang (Frontiers in Bioengineering and Biotechnology, 2019)
Rhamnolipids (RLs) are important bioproducts that are regarded as promising biosurfactant for applications in oil exploitation, cosmetics and food industry. In this study, the newly isolated Pseudomonas aeruginosa KT1115 showed high production of di-RLs. The highest yield of RLs by P. aeruginosa KT1115, reaching 44.39 g/L after 8 days of fermentation in a 5 L bioreactor, was obtained from rapeseed oil-nitrate medium after process optimization. Furthermore, we established a new separation process that achieved up to 91.82% RLs recovery with a purity of 89% and further obtained mono/di-rhamnolipids. Finally, ESI-MS analysis showed that the RLs produced by strain KT1115 have a high proportion of di-RLs (mono-RLs : di-RLs = 11.47 : 88.53), which have a lower critical micelle-forming concentration (8 mN/m) and better emulsification ability with kerosene (52.1% EI24) than mono-RLs (167 mN/m and 41.4% EI24, respectively). These results demonstrated that P. aeruginosa KT1115 is a potential industrial producer of di-RLs, which have improved applicability and offer significant commercial benefits.